Pemberdayaan Masyarakat Lokal Melalui Komposter Sebagai Alternatif Pengolahan Limbah Sampah Rumah Tangga - Agus Supriyanto; Naufal Prayoga Adistya; Cicilia Prima Jati Respati; Sofi Qhusnul Qotimah; Istiningtyas Haryadi Putri; Umi Khofifah Azzahro; Bintang Axel Agusta; Laeli Shifa Nurfauziah; Dionisius Owens; Masindah Nahar Kanaya (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Organic waste generated from household activities such as food scraps, vegetables, and fruit peels contributes significantly to the increasing volume of municipal waste. Improper management of organic waste can cause environmental problems including unpleasant odors, greenhouse gas emissions, and increased pressure on landfill sites. Therefore, simple and sustainable waste management methods are needed at the household level. This study aims to introduce and evaluate the use of a stacked bucket composter as a practical solution for processing household organic waste. The method used in this study involves the design and implementation of a stacked bucket composting system consisting of several plastic buckets arranged vertically, where the upper bucket functions as the main composting chamber and the lower bucket collects the liquid produced during decomposition. Organic waste is added regularly and supported by natural decomposing agents to accelerate the composting process. The findings show that the stacked bucket composter can effectively reduce household organic waste while producing solid compost and liquid organic fertilizer that can be utilized for plant growth. The system is relatively inexpensive, easy to construct, and suitable for limited residential spaces. The implication of this study indicates that the adoption of stacked bucket composters can encourage community participation in sustainable waste management and contribute to environmental conservation by reducing the amount of organic waste disposed of in landfills.